Size limitations on achieving tough and healable fibre reinforced composites through the use of thermoplastic nanofibres. (September 2018) - Cohades, Amaël; Daelemans, Lode; Ward, Charlie; Meireman, Timo; Van Paepegem, Wim; De Clerck, Karen; Michaud, Véronique
Abstract: Phase-separated blends of epoxy and poly(ε-caprolactone) (PCL) provide crack repair in composites after a thermal treatment at 150 °C, but decrease the material's fracture toughness. This article investigates the combination of healing with interlaminar fracture toughness improvement using electrospun PCL nanofibrous veils, interleaved between glass fibre reinforcement layers. Cure temperature close to PCL melting leads to both phase-separated domains and intact nanofibre regions. With the fast cure kinetics of the epoxy resin, phase-separated domains consist of small epoxy particles (1–5 μm diameter) surrounded by a PCL matrix. Interlaminar crack propagation in Mode I demonstrates up to 48% toughness increase when 30 g/m 2 of nanofibres are inserted between each layers. Thermal treatment however results in limited healing due to slow flow of PCL in the narrow channels. Further insight is provided regarding the channel width and polymer viscosity requirements to provide a microstructure efficient for both crack healing and interlaminar toughness improvement.